The effect of distributive justice climate on virtual team performance: A moderated mediation model - Yu, Xuan; He, Bin; Liu, Meilin; Wang, Ai; Yuan, Yue (Frontiers in Psychology, 2022)
Based on the social interdependence theory and proactive personality theory, the study collected a lot of sample data include 327 virtual team members of 75 high-tech enterprises in southwestern China to test the hypothesis. The results show that:(1)Both distributive justice climate and High quality relationships has a significant positive impact on virtual team performance;(2)High quality relationships mediates the relationship between distributive justice climate and virtual team performance.(3)Team proactive personality positively plays the moderating effect between distributive justice climate and High quality relationships.(4)Team proactive personality strengthens the indirect effect of distributive justice climate on virtual team performance through High quality relationships. The above empirical results have important theoretical significance for the construction of team atmosphere, the selection of personnel and the enhancement of virtual team performance.